Distinctive features: phonological underspecification in representation and processing - Lahiri, A; Reetz, H (Elsevier, 2010)
Phonological variation of any sort (determined by speech styles, phrasing, or morphophonological rules) affecting the shapes of words and morphemes are a matter of concern for theories of speech perception and language comprehension. To come to grips with parsing the speech stream, accessing the lexicon and ultimately recognizing words, both representational as well as processing issues must be considered. The central questions in the research presented here are: What is represented in the mental lexicon? How is it represented? How is the speech signal parsed and information mapped onto the mental lexicon? In this paper we will address four issues within the framework of our Featurally Underspecified Lexicon model (FUL): (a) our assumptions concerning distinctive features organization defined by phonological, perceptual and acoustic constraints; (b) specification of features in the mental lexicon (based on universal and language specific requirements); (c) extracting distinctive features from the signal; (d) mapping features from the signal to the lexicon. We claim that phonological features are extracted from the variable acoustic signal based on broad acoustic properties. A three-way matching algorithm maps these features onto highly abstract phonological mental representations. We provide evidence from synchronic phonological analyses, language change, psycholinguistic and neurolinguistic data.